2020
DOI: 10.3389/fonc.2020.582884
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-Induced Modulation of the Tumor Microenvironment: New Opportunities for Cancer Therapies

Abstract: Advances in immunotherapy have achieved remarkable clinical outcomes in tumors with low curability, but their effects are limited, and increasing evidence has implicated tumoral and non-tumoral components of the tumor microenvironment as critical mediators of cancer progression. At the same time, the clinical successes achieved with minimally invasive and optically-guided surgery and image-guided and ablative radiation strategies have been successfully implemented in clinical care. More effective, localized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 144 publications
(143 reference statements)
0
25
0
Order By: Relevance
“…RT is a well-known immune modulator that can provide danger signals to awaken the immune system [ 19 , 21 , 22 ]. Numerous preclinical cancer models including our research in brain and prostate tumor models have shown that RT can change the TME [ 22 , 28 , 32 , 33 , 34 , 35 , 36 , 37 ] and provoke anti-tumor immune responses locally and systemically [ 26 , 28 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RT is a well-known immune modulator that can provide danger signals to awaken the immune system [ 19 , 21 , 22 ]. Numerous preclinical cancer models including our research in brain and prostate tumor models have shown that RT can change the TME [ 22 , 28 , 32 , 33 , 34 , 35 , 36 , 37 ] and provoke anti-tumor immune responses locally and systemically [ 26 , 28 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Radiotherapy (RT) is an immune modulator [ 19 , 20 , 21 , 22 ]. Clinical cases showed the addition of RT to anti-CTLA-4 treatment significantly prolonged the survival of advanced melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor growth, invasion, and metastasis are generally affected by the interactions between the tumors and their respective microenvironments (87). Understanding these bidirectional interactions between the tumor cells and the environment could open up therapeutic targets and regimes in liver cancer treatment (88)(89)(90). Although VD influences angiogenesis, metastasis, and cancer progression in TME, the active form of VD, 1, 25 (OH) 2 D 3 modulates a couple of stroma cells explicitly, suppresses tumor growth, and act as an anti-inflammatory agent within the TME, leading to cancer reduction (91).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Once lymphocytes have been activated, they begin a metabolic transition from oxidative phosphorylation to aerobic glycolysis. Immune and tumor cells compete within the tumor microenvironment, and increased nutrient consumption by tumor cells achieves an immunosuppressive microenvironment by hindering T cell metabolism [ 151 ]; hence, interest in targeting both tumor and T cell metabolism exists, which can enhance immunity and improve the success of immunotherapies [ 152 ].…”
Section: Intervention Opportunities From a Metabolic View Of Cancermentioning
confidence: 99%
“…Glucose is a critical substrate for effector T cells and M1 macrophages, which both require aerobic glycolysis for their activation and full antitumor effector functions. Immunometabolism is therefore highlighted as a promising field in energy dysfunction treatment and tumor macroenvironment reprogramming [ 151 ]. Remarkably, immunotherapy action interconnects metabolic and immune regulation, diet [ 154 ], physical exercise, sleep, microbiota [ 155 ], and age [ 156 ], making these fundamentals of the macroenvironment a vital companion in comprehensive treatment of tumor energetic dysfunction.…”
Section: Intervention Opportunities From a Metabolic View Of Cancermentioning
confidence: 99%